Sports injuries and illnesses their prevention and treatment - O'Connor, Robert (Crowood press, 1998)
Sports Injuries and Illnesses is an essential companion for all athletes who take their general health and well-being seriously. Topics include analysis of the physical body, its strengths, and its weaknesses; study of the environment and its effect on the body; psychological implications of injury and illness; dangers of overtraining and poor nutrition; and first aid.